Relaxation of chipboard beams - analysis of results of exploratory research = Relaksacja belek z płyt wiórowych - analiza wyników badań rozpoznawczych - Socha, Tomasz; Kula, Krzysztof; Denisiewicz, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents results of experimental tests and a theoretical analysis of the phenomenon of relaxation of chipboard beams. Three linearly viscoelastic rheological models were used for mathematical modeling of the rheology of the studied material. The constants of models were determined using experimental tests and the method of least squares.
Keywords: linear viscoelasticity; wood-based materials; relaxation; rheology; lepkosprężystość liniowa; materiały drewnopochodne; relaksacja; reologia